THE INFLUENCE OF COMPENSATION, INTERNAL CONTROL, AND ACCOUNTING INFORMATION SYSTEMS ON THE PERFORMANCE OF THE ACCOUNTING DEPARTMENT OF 4-STAR HOTELS IN BADUNG REGENCY - Cokorda Istri Agung Evita Nindia Putri; Putu Novia Hapsari Ardianti (Pustaka Bangsa Indonesia, 2026)
The Accounting Department plays a vital role in the hospitality industry by providing accurate and relevant financial information to support managerial decision-making. Improving its performance requires factors such as compensation, internal control, and accounting information systems. This study examines the effects of compensation, internal control, and accounting information systems on the performance of Accounting Departments in 4-star hotels in Badung Regency. Using a quantitative survey approach, data were collected through questionnaires distributed to Accounting Department employees. A total of 226 valid questionnaires were analyzed using multiple linear regression. The results reveal that compensation, internal control, and accounting information systems each have a positive and significant effect on Accounting Department performance. Simultaneously, these variables also significantly influence performance. The findings suggest that fair compensation, effective internal control, and adequate accounting information systems contribute to improving Accounting Department performance in 4-star hotels in Badung Regency.